PERANCANGAN ALAT PENGEPRESAN JENANG DENGAN METODE ANTROPOMETRI DAN ERGONOMI (STUDI KASUS DI UKM AGAPE PEMALANG) - Nurrohman Nurrohman; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2017)
Good product design is to pay attention to convenience side by referring to anthtropometry and ergonomics approach. Jap pressing tools in UKM AGAPE Pemalang still using simple tools require workers manually by pressing a well-cooked jenang with the help of wooden entong as a tool to flatten the jenang. Many weaknesses by using the previous pressing tools that cause the worker menjdi tired quickly. In this design using anthropometri and ergonomics approach in determining worker comfort level. Sample used from 31 employees. From this research it can be concluded that with the existence of worker pressing tools more comfortable to use the tool, besides more effective than the previous tool. As for suggestions that can be given is to pay more attention to creativity, creativity, innovation, and comfort levels of workers with the concept of ergonimis in order to produce the design results of a good product. In product design in addition to considering the ergonomic size should also pay attention to the strength and security when used.Keywords:Jenang Pressing Tool, Product Design, Anthropometry